Investment Opportunity Set And Corporate Social Responsibility On Company Value - Adelia Kintan Kusuma; Diyah Santi Hariyani; Liliek Nur Sulistyowati (GOVERNORS, 2022)
The purpose of this study was to determine the effect of investment opportunity set and corporate social responsibility on firm value. This research is a type of secondary data quantitative research. The population used in this study is the infrastructure companies listed on the IDX. The sampling technique used was purposive sampling, in order to obtain 15 infrastructure companies over a 5-year period which were used as research samples. The data collection method is done by accessing the annual reports listed on the IDX and published by each infrastructure company on their respective websites. The data obtained is then processed with the help of SPSS 21 software. The results of this study indicate that the investment opportunity set affects firm value. Corporate social responsibility has no effect on firm value.